An Investigation of Pull and Push Factors in the Commercialization Policy of Electric Motorcycles in Indonesia - Fiky Two Nando; I Ketut Gunarta; Putu Dana Karningsih (Automotive Experiences, 2025)
The ongoing energy crisis underscores the pressing need for more efficient energy utilization, particularly in the transportation sector. In this regard, the shift from conventional fossil fuels to electric vehicles (EVs) is essential for achieving both environmental sustainability and energy efficiency. Several developing countries, including Indonesia, have introduced regulations to promote EV adoption. However, electric motorcycle sales remain stagnant due to persistently low adoption rates. The primary challenge lies in the limited success of commercialization efforts, which continues to hinder broader market penetration in Indonesia. This study aims to identify research opportunities that can support the commercialization of EVs in Indonesia and to explore the push and pull factors influencing this process. An exploratory approach is employed, incorporating bibliometric analysis using R 4.3.1, a scoping literature review, and in-depth interviews with EV experts. The bibliometric analysis highlights the considerable development potential of electric motorcycle commercialization. From in-depth interviews with eleven experts, forty-four influencing factors were identified: twenty-nine of which are newly emerging factors, and fifteen are already established in the literature. Among these, four pull factors were confirmed, while twelve push factors were consistently highlighted by the experts. “Inexpensive product price for consumers” emerged as the most dominant pull factor in accelerating electric motorcycle commercialization, whereas the provision of incentives was the most frequently emphasized push factor driving supportive commercialization policies.